Secondary homonymy in Bryozoa: the case of Reteporella jullieni (Cheilostomatida) - J., Souto (Zootaxa, 2019)
The name Reteporella jullieni is currently used to designate two different species of bryozoans from Atlantic deep waters, Reteporella jullieni (Calvet, 1907), described originally as Retepora arborea from the northwest of Spain, and Reteporella jullieni Calvet, 1931, described from the Azores. Successive changes in the genus assignation of the first species, until its current inclusion in the genus Reteporella, have caused the present situation. This represents a case of secondary homonymy as described in the International Code of Zoological Nomenclature. Here, a new name (Reteporella azorensis nom. nov.) is proposed for Reteporella jullieni Calvet, 1931, following the principle of priority. Both species are re-described, and lectotypes and paralectotypes are selected.